Strategies of airway management for head and neck photo‐dynamic therapy. Issue 6 (15th June 2013) - Story, William; Sultan, Ahmed A.; Bottini, Gian; Vaz, Francis; Lee, Gene; Hopper, Colin
Abstract Introduction Photodynamic therapy (PDT) is a minimally invasive treatment modality which has great clinical implications, especially in head and neck oncology. Post‐operative swelling is a well‐documented consequence of PDT. It is paramount the airway remains patent for these patients. A tracheostomy remains the gold standard treatment modality for base of tongue tumours susceptible to post operative PDT inflammation, which can lead to a compromised airway. We have carried out a retrospective study to outline the airway management strategies employed for head and neck cancer patients treated with PDT and suggest recommendations for future management. Materials and Methods This retrospective clinical study utilises 88 patients (53 males and 35 females) treated at the UCLH Head and Neck Center, London (between 2006 and 2013), for treatment of various lesions with superficial and/or interstitial PDT, when the airway could potentially be compromised. Results Of the 88 patients selected 60 had interstitial PDT (iPDT) and 13 had superficial PDT (sPDT). Fifteen patients were treated with both iPDT and sPDT. Among the iPDT patients 19 had a trachestomy; two patients a Quicktrach; four a Cook Airway Exchange Catheter (CEAC); one a percutaneous tracheostomy; one a needle tracheostomy and 33 patients did not receive any temporary airway pathways. Among the sPDT patients two had a trachestomy. Although the majority of patients did not suffer any major incidents, one sPDT patient required an emergency tracheostomy two days post‐operatively. Conclusion Airway management is vital when planning PDT treatment for tongue based tumours. Consider a more conventional approach when the lesion being targeted is located at a higher risk site: Floor of mouth/posterior tongue/tongue base or when multiple oral sites are being treated. Lasers Surg. Med. 45:370–376, 2013. © 2013 Wiley Periodicals, Inc.